Parents with mental illness – a qualitative study of identities and experiences with support services. Issue 8 (8th August 2016) - Jones, M.; Pietilä, I.; Joronen, K.; Simpson, W.; Gray, S.; Kaunonen, M.
Accessible summary: What is known on the subject?: According to estimates more than half of adult mental health service users are parents, but their experiences are largely lacking from research literature. Parental mental illness can often be viewed from a risk perspective. Parents with mental illness and their families have unmet support needs. What this paper adds to existing knowledge?: Parents with mental illness want acknowledgement that they can be able and responsible. Many parents adopt an expert by experience identity. Fathers can feel their parental role is not recognized and mothers express fears of being judged if they discuss their illness. What are the implications for practice?: Adult mental health services need to recognize and support parental role of service users. Joint care planning and family oriented care should be promoted. Professionals should take advantage of the knowledge of these parents and they could be more actively engaged in service development. Abstract: Introduction: Parental mental illness is often viewed from a risk perspective. Despite this, being a parent can be both valuable and motivating. Research literature lacks the perspective of mothers and fathers, who have experienced mental illness. Aim: This study explores how parents with mental illness construct their identities as mothers and fathers and their experiences with health and social care services. Method: Three focus groups with 19 participants were conducted in Finland and Scotland. Methods of discourse analysis have been used in to analyse the interview data. Results: Adult service users want their parenting role recognized and supported. Parents have knowledge and skills which can be utilized and many have adopted an expert by experience identity. Discussion: Being able to see oneself as a 'good' parent can be challenging but important. Parents may require support, but want to be included in the planning of their care. Services could make more use of the knowledge and skills parents and families have, and joint working could lessen parents' anxieties. Implications for practice: Mental health practitioners are in a key position in providing more family centred, resource focused care. Service user expertise should be acknowledged in clinical practice.